Progressive Pathway to Universal Health Coverage in Tanzania : A Call for Preferential Resource Allocation Targeting the Poor - Wang, Huihui; Juma, Mariam Ally; Rosemberg, Nicolas; Ulisubisya, Mpoki M. (Taylor and Francis, 2019)
Universal health coverage (UHC) can be a vehicle for improving equity, health outcomes, and financial well-being. After publication of the World Health Organization’s report in 2010, many countries declared their goal of achieving UHC. A key lesson from research evidence and country experience in implementation of pro-poor UHC is that public budget plays a crucial role in financing the poor. It has long been recognized that if a country wants to reduce the gap between the poor and non-poor, deprived groups should receive preferential allocation of health care resources to achieve more rapid improvements in their health. Based on a technical analysis of public funds allocation mechanisms in Tanzania, we argue that these mechanisms should prioritize the poor more explicitly and give them preferential treatment to close the gap with the non-poor in service utilization and health outcomes.